2015
DOI: 10.1177/1557988315619470
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Male’s Perspectives of Health Behaviors Related to Weight Management

Abstract: Hispanic males have the highest prevalence of overweight and obesity among men in the United States; yet are significantly underrepresented in weight loss research. The purpose of the current study was to examine Hispanic male’s perspectives of health behaviors related to weight management to refine the methodologies to deliver a gender-sensitive and culturally sensitive weight loss intervention. From October 2014 to April 2015, semistructured interviews were conducted with 14 overweight Hispanic men of ages 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 46 publications
3
63
0
Order By: Relevance
“…In our study, researchers conducted individual semi-structured interviews with Hispanic men prior to developing the study, which identified several viable gender-and culturallytailored recruitment and intervention strategies (e.g. face-to-face individual counseling sessions, inviting spouses to attend sessions) (Garcia et al, 2017). These strategies were then incorporated into the design of the current pilot study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, researchers conducted individual semi-structured interviews with Hispanic men prior to developing the study, which identified several viable gender-and culturallytailored recruitment and intervention strategies (e.g. face-to-face individual counseling sessions, inviting spouses to attend sessions) (Garcia et al, 2017). These strategies were then incorporated into the design of the current pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…These elements include the following: (1) language, (2) persons, (3) metaphors, (4) content, (5) concepts, (6) goals, (7) methods, and (8) context. Given the extent of interactions between gender and cultural factors in our sample (Garcia et al, 2017;Valdez et al, 2017), a great deal of the tailoring for gender and culture occurred simultaneously. For example, within the element of context, which considers a participants broader social, economic, and political reality, discussions were held during intervention sessions related to gender role strain and perceived challenges providing healthy foods for family members.…”
Section: Gender and Cultural Tailoring Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Latino/Hispanic population is constantly increasing and its health concerns are being studied, there is little research about the Latino men health status and decision-making. Concerning Latino/ Hispanic males in particular, adequate access to health education can be lifesaving and recent studies show that this group is more likely to die from diabetes, chronic liver disease, liver cancer [3,8] and human immunodeficiency virus/acquired immunodeficiency syndrome [1].…”
Section: Latino Men Health Decision Making and Use Of Health Care Sermentioning
confidence: 99%